Weighting the SOEP-CoV study 2020 - Rainer Siegers; Hans Walter Steinhauer; Sabine Zinn (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This paper details the sampling design, results from the field, analysis of selectivities, as well as raking procedures used in the SOEP-CoV study. The sample consists of a random selection of 12,000 households in the Socio-Economic Panel Study (SOEP). The sample was divided and surveyed in nine successive tranches. The largest tranches were surveyed first starting April 1, 2020. By the end of May, all of the smaller remaining tranches had been surveyed.
Keywords: 330; Coronavirus; Panel; Stichprobenerhebung; Deutschland